2021
DOI: 10.1007/s00248-021-01879-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevational Changes in Bacterial Microbiota Structure and Diversity in an Arthropod-Disease Vector

Abstract: Environmental conditions change rapidly along elevational gradients and have been found to affect community composition in macroscopic taxa, with lower diversity typically observed at higher elevations. In contrast, microbial community responses to elevation are still poorly understood. Specifically, the effects of elevation on vector-associated microbiota have not been studied to date, even though the within-vector microbial community is known to influence vector competence for a range of zoonotic pathogens. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…For microbiomes, in Anna's hummingbirds the relative abundance of certain bacterial lineages and the overall composition of faecal microbiomes vary with elevation, but microbiome diversity at the individual host level (e.g., the number of bacterial lineages) does not (Herder et al, 2021). A decrease in diversity with elevation was detected in bacterial communities associated with the sheep tick (Aivelo et al, 2021). Skin microbiome diversity also decreases with elevation in humans (Li et al, 2019), but increases with elevation in salamanders (Wolz et al, 2018) and shows no elevational trend in Puerto Rican frogs (Hughey et al, 2017).…”
Section: Open Eco‐evolutionary Questions In Microbiome Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For microbiomes, in Anna's hummingbirds the relative abundance of certain bacterial lineages and the overall composition of faecal microbiomes vary with elevation, but microbiome diversity at the individual host level (e.g., the number of bacterial lineages) does not (Herder et al, 2021). A decrease in diversity with elevation was detected in bacterial communities associated with the sheep tick (Aivelo et al, 2021). Skin microbiome diversity also decreases with elevation in humans (Li et al, 2019), but increases with elevation in salamanders (Wolz et al, 2018) and shows no elevational trend in Puerto Rican frogs (Hughey et al, 2017).…”
Section: Open Eco‐evolutionary Questions In Microbiome Researchmentioning
confidence: 99%
“…Latitudinal diversity gradient Decrease in diversity with latitude Temperature, productivity, diversification and extinction rates, dispersal rates Traditional LDG (Dikongue & Segurel, 2017;Neu et al, 2021;Suzuki et al, 2020;Thompson et al, 2017) • Stronger LDG for external microbiomes • Stronger LDG across larger latitudinal range • LDG differs for aquatic and terrestrial environments Inverse LDG (Neu et al, 2021;Thompson et al, 2017) No LDG (Corby-Harris et al, 2007;Morelan et al, 2019) Elevational diversity gradient Decrease in diversity with elevation or diversity peak at intermediate elevations Temperature, precipitation, habitat area, competition, time since first colonization, dispersal rates Lower microbiome diversity at higher elevation (Aivelo et al, 2021;Li et al, 2019) • Stronger EDG for external microbiomes • Decrease in diversity with elevation • EDG driven by variation in host ecology and demography…”
Section: Possible Expectations For Microbiome Biogeographymentioning
confidence: 99%
“…Recent studies have increasingly shown that the tick microbiome varies by geographical origin, species, sex, life stages, environmental stress, tick immunity, host and blood meal [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In particular, the results showed that tick-associated bacterial communities are largely species-specific, and microbiota of nymphs and males appeared to be more diverse than those of adult females [ 7 , 9 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have increasingly shown that the tick microbiome varies by geographical origin, species, sex, life stages, environmental stress, tick immunity, host and blood meal [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In particular, the results showed that tick-associated bacterial communities are largely species-specific, and microbiota of nymphs and males appeared to be more diverse than those of adult females [ 7 , 9 , 10 , 12 ]. The findings of several studies revealed that tick samples originating from geographically close locations had shown higher microbiome similarity [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation